2010
DOI: 10.1155/2010/454792
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Sarcomatoid Carcinoma (Carcinosarcoma) of the Urinary Bladder: Analysis of 221 Cases

Abstract: Background. Urinary bladder sarcomatoid carcinoma (carcinosarcoma) is rare. The objective of this study was to examine the epidemiology, natural history, and prognostic factors of urinary bladder carcinosarcoma using population-based registry. Methods. The Surveillance, Epidemiology, and End Results (SEER) Program database was used to identify cases by tumor site and histology codes. The association between clinical and demographic characteristics and long-term survival was examined. Results. A total of 221 hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
117
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(126 citation statements)
references
References 31 publications
4
117
0
5
Order By: Relevance
“…Most sarcomatoid carcinomas in hollow viscus are polypoid and pedunculated (6,7). The occurrence of this tumor in nasal cavity and paranasal sinus is rare (8), with only 15 cases reported in the English literature (4,8,9).…”
Section: Discussionmentioning
confidence: 99%
“…Most sarcomatoid carcinomas in hollow viscus are polypoid and pedunculated (6,7). The occurrence of this tumor in nasal cavity and paranasal sinus is rare (8), with only 15 cases reported in the English literature (4,8,9).…”
Section: Discussionmentioning
confidence: 99%
“…From 1988 to 2003, only 0.09% of high grade bladder cancers were CS, and the age-adjusted incidence was 2 per 10,000,000 persons per year. 9 CS in the bladder occurs more often in elderly men and is a highly malignant tumor, with a greater risk of death than urothelial carcinoma. 10 CS of the upper urinary tract is even rarer, with only 12 cases reported until 2006, 11 compared to 14 cases of CS of the renal pelvis.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of sarcomatoid carcinoma must be considered in all adult patients with malignant spindle cell tumor of the bladder, unless proven otherwise. The recognition of sarcomatoid carcinomas has great therapeutic and prognostic significance (Wang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Although the combination of gemcitabine and cisplatin is a well-tolerated combination in advancedstage urothelial carcinoma patients, the literature contains few cases regarding its use in carcinosarcoma. Some researchers reported that they obtained good results with ovarian-or sarcoma-type chemotherapy regimens (Wang et al, 2010). We used a systemically administered combination of gemcitabine and cisplatin regimen in the presented cases.…”
Section: Discussionmentioning
confidence: 99%